The influence of principal leadership style, infrastructure, and work climate on teachers’ performance - Wulan Gontina; Happy Fitria; Alfroki Martha (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The aim of this study is to determine the effect of the leadership style, infrastructure, and work climate of the principal on teachers’ performance. With a descriptive approach, this approach involves quantitative methods. 105 participants consisted of the researh population. There were 79 people in the research sample. In this research, the sampling technique is Simple Random Sampling. The technique of using a questionnaire was used to gather data. Using a Likert Scale to weigh values. Validity, reliability, descriptive analysis, inferential analysis (prerequisite test and classical assumption test), multiple linear regression analysis, hypothesis analysis (t test and F test) and determination coefficient analysis were used to analyze the results. The findings showed that the leadership style of the principal, infrastructure advice, and work climate had a substantial influence on teachers' performance of SMP Negeri in the Sembawa District partially and simultaneously.